Kebebasan Perempuan dalam Novel dan Film Yuni - Kamila, Zahra Adni (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
The film Yuni is an adaptation of the novel Yuni written by Ade Ubaidil. Through the screenplay by Kamila Andini, this film managed to win several awards and special screenings all over the world which produced proud results in the world of Indonesian cinema. Apart from the film Yuni, the novel with the same title also received quite good appreciation from readers after the film was released. The film and novel Yuni tells the story of the journey of a woman named Yuni who fights for her dream of higher education but is restrained by society's perspectives and stigma. This film and novel raise interesting issues that represent all women's voices regarding their freedom of rights. This research aims to describe the freedom exercised by the character Yuni in facing bad perspectives and stigma from society. This research uses a comparative literature method with a feminist approach. The results of this research show that the character Yuni, whether in the novel or film, has the characteristics of being brave, responsible, determined, adhering to principles, and being able to voice her opinion which interprets women's freedom in making choices.